Oil geochemistry of Cretaceous Bima Formation shales in Gongola sub-basin, Northern Benue Trough, Nigeria (Journal of Pure and Applied Sciences (Science Forum), 2026)
Prospective source rocks (shales) of the Bima Formation in the Gongola sub-basin, Northern Benue Trough, Nigeria, were studied in the field and laboratory to increase our understanding on their hydrocarbon-generating potential, thermal maturity, and paleo-depositional environment. Results obtained from the field studies suggest that the Bima Formation was deposited in a fluvial setting owing to the absence of marine fossils and presence of ferruginized beds. Other attributes of the fluvial settings observed include mud cracks and poor sorting, implying textural immaturity. Results of the geochemical analysis obtained show that the studied shales are rich in organic matter, and inferred to have mostly kerogen type II–III and type III, which may be able to yield mixed oil and gas and gas, respectively. The trisnorhopane thermal maturity (trisnorneohopane/trisnorhopane) values of the studied shales vary between 0.88 and 1.12, implying that the studied shales are within the oil window. Also, cross-plot of C29 steranes epimer ratios versus C32 homobopanes epimer ratios range from 0.46 to 0.48, suggesting that all the source rocks are thermally mature. The Pr/n-C17 versus Ph/n-C18 cross-plot and the steranes ternary plot revealed that oil extracted from the studied shale samples originated from organic matter of both marine and terrestrial sources (mixed organic matter) and was deposited under anoxic and suboxic conditions.